Integrating Raman spectroscopy and optical meters for nitrogen management in broccoli seedlings - Tuccio, Lorenza; Cacini, Sonia; Arati, Giulia; Distefano, Carmelo; Traversari, Silvia; Fontanelli, Giacomo; De Nicola, Gina Rosalinda; Matteini, Paolo (Frontiers in Plant Science, 2025)
Raman spectroscopy enables non-destructive detection of nitrates and other nitrogen-related biochemical markers, including chlorophyll and polyphenols, with unparalleled specificity and sensitivity. Integrating Raman spectroscopy with proximal optical sensors, such as Dualex (Dx) and Multiplex (Mx), offers a transformative approach to precision nitrogen management in broccoli seedlings, complementing their ability to rapidly estimate nitrogen balance indices and key vegetation compounds. The integration demonstrated strong correlations between Raman spectral bands, optical indices, and biochemical parameters across varying nitrogen levels, enhancing the precision of nitrogen status assessment, resulting in a robust, scalable, and information-rich system. By combining molecular-level detail with practical field applications, this hybrid strategy represents a significant advancement in sustainable agriculture. Future research will explore the applicability of this integrated methodology to other plant species.